Causal Relations on Beneficial and Non-beneficial Factors for A Supplier Selection Problem - V. Reza Bayu Kurniawan (Universitas Sarjanawiyata Tamansiswa, 2021)
Identifying the relationship between criteria in the supplier selection problem (SSP) decision making is a challenging as it brings many impacts to supplier performance as well as ensuring end-products’ quality. However, evaluating the supplier selection factors in terms of beneficial and non-beneficial criteria is worth-exploring. This study aims to analyze the causal relations between supplier selection factors categorized into beneficial and non-beneficial criteria. A case study in a medium-sized paper manufacturer in Indonesia involving three decision-makers (DMs) in procurement and manufacturing division is proposed. Since the problem is often considered as an multi-criteria decision-making (MCDM) problem, the DEMATEL method is utilized to illustrate the cause-and-effect relationship between factors in an impact-relation map. Initially, ten factors were identified based on the five initial criteria, while six and four factors are included in beneficial and non-beneficial group, respectively. The result indicated that the three factors, namely complaint networks, integrity, and on-time delivery, were identified as effect factors, whilst the remaining factors were cause factors. This study recommend the DMs to focus on the strongest influencing factors to determine the supplier performance. Additionally, they are also able to determine the different approaches pertaining to SSP considering factors’ characteristics.